Pengaruh Personal Selling, Brand Image, dan Kualitas Produk Terhadap Kepercayaan (Trust) Konsumen dan Dampaknya Pada Keputusan Pembelian Polis Asuransi - Alvin Yosua (CV. Syntax Corporation Indonesia, 2021)
Insurance is a mechanism of protection against property owned where there is an insured party who pays a certain amount of premiums to the insurer to get compensation for the risks that may occur in the future. This study aims to determine the effect of earnings management and information assimilation on the cost of equity. This quantitative research uses secondary data and the sampling method in the form of purposive sampling, obtained 100 consumer goods companies listed on the IDX from 2015- 2019 as samples. Processing of data analysis using SPSS version 23 software. The results show that earnings management and information asymmetry partially do not have a significant effect on cost of equity. Likewise, together it shows that earnings management and information asymmetry do not have a significant effect on the cost of equity. It is hoped that this research can provide information to shareholders about the importance of making more observations on the quality of the company's financial statements so that they are not wrong in making investment decisions